Effectiveness of the Cooperative Learning Method in English Subjects in Higher Education - Kalangi, Jola S; Nurhikmah, Nurhikmah; Suyadi, Suyadi; Rais, Rinovian; Widya Fransiska, Fini (International Journal of Language and Ubiquitous Learning, 2024)
Background. Cooperative learning methods have become the main focus in efforts to improve learning outcomes at the tertiary level, especially in English subjects. Its use is believed to provide a more dynamic and interactive learning environment, enabling students to develop English language skills holistically. Purpose. This research aims to explore the effectiveness of cooperative learning methods in English language subjects at universities, with a focus on speaking, listening, and understand English. Method. This research uses a quantitative approach with an experimental research design. Two groups of students consisting of the experimental group (applying the cooperative learning method) and the control group (applying the conventional method) were given speaking, listening and understanding English ability tests before and after the learning intervention. Results. Data analysis showed that the cooperative learning method had a significant improve students' speaking, listening and understanding English skills in higher education. The average score of the experimental group on tests of speaking, listening and understanding English was significantly higher than that of the control group. Conclusion. In the context of English subjects in higher education, cooperative learning methods have proven to be effective in improving student learning outcomes. Their use can enrich learning experiences, increase social interactions, and prepare students for success in an increasingly connected global environment. It is hoped that further support and application of this method can strengthen the quality of English language learning in higher education.